2019
DOI: 10.1037/ebs0000137
|View full text |Cite
|
Sign up to set email alerts
|

Father absence, age at menarche, and sexual behaviors in women: Evaluating the genetic confounding hypothesis using the androgen receptor gene.

Abstract: Life history theory posits father absence and associated stressors are key for regulating the development of reproductive phenotypes. The causal status of father absence has been questioned, however, because genetic confounding can account for this association. The purpose of the current study was to replicate and extend prior work that evaluated the androgen receptor gene’s (AR) contribution to the interrelations between father absence and daughters’ age at menarche (AAM) and sexual behaviors by evaluating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Moreover, the non-significant effect of shared environmental factors (i.e., C) suggests that not only did father absence and other measured environmental factors play no significant role in menarche timing; no unmeasured factors that varied between families played such a role either. Also consistent with this conclusion are findings from studies using candidate gene (Schlomer et al, 2019) and polygenetic score (Gaydosh et al, 2018) approaches, which have not supported the genetic confounding hypothesis. A more conclusive test of the genetic confounding hypothesis in future research should use a higher-powered twin study or Genome Wide Association Study (GWAS) to provide more accurate genetic correlation estimates between father absence and menarche timing variables, which could then be used to directly test the simulation-model predictions presented by Barbaro et al (2017).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, the non-significant effect of shared environmental factors (i.e., C) suggests that not only did father absence and other measured environmental factors play no significant role in menarche timing; no unmeasured factors that varied between families played such a role either. Also consistent with this conclusion are findings from studies using candidate gene (Schlomer et al, 2019) and polygenetic score (Gaydosh et al, 2018) approaches, which have not supported the genetic confounding hypothesis. A more conclusive test of the genetic confounding hypothesis in future research should use a higher-powered twin study or Genome Wide Association Study (GWAS) to provide more accurate genetic correlation estimates between father absence and menarche timing variables, which could then be used to directly test the simulation-model predictions presented by Barbaro et al (2017).…”
Section: Discussionmentioning
confidence: 83%
“…Results of investigations attempting to parse out genetic influences to assess the robustness of effects of life history antecedents on menarche timing are mixed and use varying designs. Some investigations have shown no effect of father absence on menarche once genetic variation is accounted for (D'Onofrio et al 2006;Mendle et al, 2006), whereas other investigations have not found evidence to support the genetic confounding hypothesis using sibling (Tither & Ellis, 2008), candidate gene (Schlomer et al, 2019) or polygenic score approaches (Gaydosh et al, 2018). Each of these investigations, however, include only a narrow set of environmental or genetic variables.…”
Section: Assess For Genetic Confounding Of Associationsmentioning
confidence: 99%
“…Compared with extensive evidence that father absence predicts early menarche, no known studies have systematically reviewed and synthesized the mediating effect of childhood stress to account for the father absence effects on early menarche. Previous studies have reported that girls raised in the absence of their fathers are more likely to reach sexual maturation at a younger age (Ellis et al, 2003 ; Anderson, 2015 ; Hehman and Salmon, 2018 ) because the link between father absence and earlier physical maturation is a part of the fast LH strategy (Belsky, 2012 ; Schlomer et al, 2019 ). In addition to the total effect of father absence on earlier onset of menarche, the present study showed that father absence and associated stressors, such as familial perturbation and harsh family environment, also affected physical development.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not replicated, however, in a pair of independent follow-up studies (Jorm, Christensen, Rodgers, Jacomb, & Easteal, 2004;Schlomer, Murray, Yates, Hair, & Vandenbergh, 2019). Notably, a bettercharacterized CAG variant within AR was related to earlier AAM independent of father absence and moderated the association between father absence and women's sexual behaviors (Schlomer et al, 2019). Although not specific to father absence, two additional primary and replication studies found that variation in the estrogen receptor-α gene (ESR1) moderated the effect of family relationships on AAM (Hartman, Widaman, & Belsky, 2015;Manuck, Craig, Flory, Halder, & Ferrell, 2011).…”
Section: Genetic Confouding In the Father Absence/aam Associationmentioning
confidence: 93%
“…An initial study on father absence and AAM found support for the androgen receptor (AR) genetic confounding hypothesis when examining the GGC variant (Comings, Muhleman, Johnson, & MacMurray, 2002). This finding was not replicated, however, in a pair of independent follow-up studies (Jorm, Christensen, Rodgers, Jacomb, & Easteal, 2004;Schlomer, Murray, Yates, Hair, & Vandenbergh, 2019). Notably, a bettercharacterized CAG variant within AR was related to earlier AAM independent of father absence and moderated the association between father absence and women's sexual behaviors (Schlomer et al, 2019).…”
Section: Genetic Confouding In the Father Absence/aam Associationmentioning
confidence: 99%